Panax Ginseng C.A.Mey. as Medicine: The Potential Use of Panax Ginseng C.A.Mey. as a Remedy for Kidney Protection from a Pharmacological Perspective - Jin, De; Zhang, Yuqin; Zhang, Yuehong; Duan, Liyun; Zhou, Rongrong; Duan, Yingyin; Sun, Yuting; Lian, Fengmei; Tong, Xiaolin (Frontiers in Pharmacology, 2021)
The observation that unhealthy diets are a significant risk factor for poor health outcomes has facilitated interest in the conception of ‘Food/Diet Supplements from Natural Sources as Medicine’. This concept is especially associated with metabolic diseases, such as kidney disease (DKD), in which food/diet supplements therapies are already used to regulate metabolic disorders and improve poor health outcomes. Increased awareness that pathological metabolites of DKD originate not only from hyperglycemic metabolism but also from chronic inflammation, immunological reaction, gut microbial metabolism, which is directly affected by Food/Diet Supplements, has inspired interest in the potential of ‘Food/Diet Supplements from Natural Sources as Medicine’ approaches in DKD beyond protein, sodium and phosphate restriction in the current medical management. Ginseng has been widely consumed as food/diet supplements from natural sources, and its therapeutic properties have also aroused widespread concern. Therapeutic properties of ginseng such as anti-inflammatory, ameliorating chronic inflammation, enhancing the immunity, resisting the oxidation again, and regulating the glucose and lipid metabolism have been widely reported. Recent years, lots of interesting studies have reported the potential use of ginseng in the management of DKD. DKD has become the leading cause of end-stage renal disease worldwide, which increases the risk of premature death and poses a serious financial burden. Although DKD is somehow controllable with different drugs such as Angiotensin-Converting Enzyme Inhibitors (ACEI), Angiotensin Receptor Blockers (ARB) and lowering-glucose agents, modern dietary changes associated with DKD have facilitated research to assess the preventive and therapeutic merits of diet supplements from natural sources as medicine including ginseng. Findings from many scientific evidences have suggested that ginseng can relieve the pathological status in cellular and animal models of DKD. Moreover, a few studies showed that alleviation of clinical phenotype such as reducing albuminuria, serum creatinine and renal anemia in DKD patients after application or consumption of ginseng. Therefore, this review aims to discuss the effectiveness of ginseng as medicine for targeting pathological phenotypes in DKD from a pharmacological perspective. This review will provide new insights into the potential understanding use of ginseng in the management of DKD in clinical settings.